2016
DOI: 10.18002/rama.v11i1.3310
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of practicing taekwondo to adolescents in Addis Ababa City, Ethiopia

Abstract: This study aimed at examining the benefits and challenges of practicing Taekwondo (TKD) to adolescents in Addis Ababa. In so doing, the study investigated the nature of TKD training, benefits of practicing TKD, and challenges/problems related with practicing TKD. A descriptive concurrent mixed methods research design was used. Accordingly, the quantitative part of the study had 108 TKD adolescent participants while the qualitative part had 12 participants (eight TKD adolescents and four TKD coaches), from four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Participation in routine Taekwondo training can provide adolescents with various physical, mental, and social benefits [ 24 ], and can be beneficial in the stress management of undergraduate students [ 16 ]. In addition, it can be effective in promoting holistic health, by inducing positive changes in body, mind, and spirit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in routine Taekwondo training can provide adolescents with various physical, mental, and social benefits [ 24 ], and can be beneficial in the stress management of undergraduate students [ 16 ]. In addition, it can be effective in promoting holistic health, by inducing positive changes in body, mind, and spirit [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of teenagers, a positive influence of practicing CS and MA on their well-being was shown. Comprehensive elements of the training help young people to meet different needs, expectations and requirements, and as a result improve their well-being [ 7 ]. Research results from existing scientific literature indicate that martial arts (karate, taekwondo, kung fu and judo) can improve some aspects of cognitive functions and neurotrophic factors (BDNF and IGF-1) associated with the work of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Regular training positively influences their well-being, personality development, and cognitive and educational functions [ 5 , 6 ]. Multidimensional benefits, such as improvement of psychophysical well-being, increased self-defense possibilities, and avoidance of addictions, were observed among teenagers practicing taekwondo [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them are cross-sectional studies exploring sporting career of athletes or how long they have been doing this sport. An analysis of the results of these studies indicated that athletes practicing taekwondo went through positive psychosocial changes (Duthie, Hope & Barker, 1978, Rothpearl, 1980Nosanchuk, 1981, Nosanchuk & Mac Neil, 1989Skelton et al, 1991;Kurian et al, 1993, Kim, 1995, Kim et al 2011, Tadesse 2016, Benke at al. 2017, Petrovic 2017.…”
Section: Introduce the Problemmentioning
confidence: 99%